PAPUA TRADITIONAL ARCHITECTURAL IDENTITY - Hasrul Hasrul; Ikaputra Ikaputra (Jurnal Arsitektur ARCADE, 2023)
Abstract: Papua as the largest island in Indonesia has a variety of traditional houses that have the characteristics of describing the local identity and uniqueness. This study uses a literature study method and aims to examine how to interpret traditional Papuan architectural works. Theoretically the result of this research finds that the identity of traditional Papuan architecture is seen from the traditional house as an architectural work in terms of firmitas, utilities, and Venustas. The similarity of shapes in various traditional Papuan houses is found on the roof in the form of a sloping roof with various shapes. There are elements of 'tradition' and 'environmental adaptation' in the architecture of traditional Papuan houses, emphasizing special meanings according to local culture.Keyword: identity, traditional architecture, traditional house, PapuaAbstrak: Papua sebagai pulau terbesar di Indonesia memiliki ragam rumah tradisional yang memiliki ciri khas menggambarkan identitas dan kekhasan lokal setempat. Penelitian ini menggunakan metode studi kepustakaan dan bertujuan untuk mengkaji secara teoritis bagaimana memaknai karya arsitektur tradisional Papua. Hasil dari penelitian ini secara teoritikal bahwa identitas arsitektur tradisional Papua dilihat dari rumah tradisional sebagai karya arsitektur dari sisi firmitas, utilitas, dan venustas. Kesamaan bentuk pada ragam rumah tradisonal Papua terdapat pada bagian atap berupa atap miring dengan bentuk beragam. Adanya unsur ‘tradisi’ dan ‘adaptasi lingkungan’ pada arsitektur rumah tradisional Papua, menitik beratkan pada pemaknaan khusus sesuai budaya setempat.Kata Kunci: identitas, arsitektur tradisional, rumah tradisional, Papua